Aicardi-Goutières Syndrome Type 1: A Novel Missense Variant and Review of the Mutational Spectrum - Tasharrofi, Behnoosh; Karimzadeh, Parvaneh; Asadollahi, Mostafa; Hasani, Sepideh; Heidari, Morteza; Keramatipour, Mohammad (Iranian Journal of Child Neurology, 2024)
Objectives Mutations in the TREX1 gene cause Aicardi-Goutières syndrome (AGS) 1, associated with a spectrum of autoimmune and neurodegenerative manifestations. AGS 1, the most severe neonatal type of AGS, is characterized by abnormal neurologic findings, visual inattention, hepatosplenomegaly, thrombocytopenia, skin rash, restlessness, and fever. Materials & Methods The present study described two affected siblings from an Iranian family whose phenotypes overlap with intrauterine infections. They had almost similar presentations, including developmental delay, microcephaly, no fix and follow epileptic seizures and the same pattern of brain CT scan involvements. Following clinical and paraclinical assessments, whole-exome sequencing was employed to determine the disease-causing variant, and subsequently, PCR-Sanger sequencing was performed to indicate the segregation pattern of the candidate variant in family members. Results Genetic analysis revealed a novel homozygous missense variant (c.461A>C; p.D154A) in the TREX1 gene in affected family members. Sanger sequencing of other family members showed the expected zygosities. Conclusion This study identifies a novel mutation in the TREX1 gene in this family and highlights the efficiency of next-generation sequencing-based techniques for obtaining a definite diagnosis in patients with early-onset encephalopathy